The Term Structure of Interest Rates: Reply - Culbertson, J. M. (Quarterly Journal of Economics, 1963)
Journal Article The Term Structure of Interest Rates: Reply Get access J. M. Culbertson J. M. Culbertson University of Wisconsin Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 77, Issue 4, November 1963, Pages 691–696, https://doi.org/10.2307/1879459 Published: 01 November 1963